The influence of chronic kidney disease and age on revascularization rates and outcomes in acute myocardial infarction – a cohort study. Issue 4 (June 2017) - Kotwal, Sradha; Ranasinghe, Isuru; Brieger, David; Clayton, Philip A; Cass, Alan; Gallagher, Martin
Background: There is a paucity of data on the complex interaction between chronic kidney disease, age and its impact on management and outcomes in acute myocardial infarction. Methods: A state based claims dataset that collects data on all hospitalizations (representing 32.3% of the Australian population) was used to identify all patients admitted with a principal diagnosis of acute myocardial infarction (ICD10 codes: I21.0–I21.4) over a four-year period. Patients were linked to the state death registry and followed until death or end of follow-up (31 December 2009). Chronic kidney disease was defined as the presence of any of 65 ICD10 diagnostic codes for chronic kidney disease. The primary outcomes were receipt of revascularization, length of hospital stay and mortality adjusted for age, comorbidities and prior revascularization at presentation. Results: Of the 40, 472 patients with acute myocardial infarction, chronic kidney disease was present in 4814 patients (11.9%). Median follow-up was 2.8 years (range 0–5.5 years). In the multivariable model, there was a marked interaction between chronic kidney disease and age ( p <0.001). Chronic kidney disease was a powerful marker of lower revascularization rates (median age group of 70–79 years: odds ratio 0.68; 95% confidence interval 0.59–0.78; p <0.001), especially in those over the age of 50 years. The impact of chronic kidney disease on length of stay (median age group of 70–79 years vs . referent age group 18–39 years: incidence rate ratio 1.41; 95% confidence interval 1.32–1.51; p <0.001) and long-term mortality (median age group of 70–79 years: hazard ratio 2.19; 95% confidence interval 2.01–2.39; p <0.001) was mitigated with increasing age. Conclusion: Chronic kidney disease is an important deterrent for the receipt of revascularization in older patients, but age is the primary determinant of length of stay and mortality.